SANKSI PIDANA BAGI PEGAWAI NEGERI SIPIL (PNS) YANG TIDAK NETRAL DALAM PEMILIHAN KEPALA DAERAH (PILKADA) KOTA BAUBAU BERDASARKAN UNDANG-UNDANG APARATUR SIPIL NEGARA - La Ode Dedi Abdullah (Jurnal Hukum Volkgeist, 2018)
in the election of the head of the area (of the elections) town of Baubau on the basis of legislation ASN. The method used is the normative research methods, the data obtained will be analyzed are descriptive. Results found is the Neutrality of CIVIL SERVANTS, is the solution to solve the problems of the participation of CIVIL SERVANTS in political parties. With the inception of law No. 2014 about 15 years of Civilian rule, State Apparatus is expected to neutralize Government and then the Government should be able to realize the regulation, thus the goal of neutrality would be achieved . Law enforcement against the neutrality of CIVIL SERVANTS, in its realization have difficulties, because the arrangements regarding law enforcement civil service neutrality which is regulated in Act No. 43 Of 1999 Staffing issues, namely article 3 and The common explanation I number 6, giving sanctions for CIVIL SERVANTS who violate this regulation be removed from civil servants, these regulations only set up for CIVIL SERVANTS and members of the Executive Board of the Centre, so that the regulation has not been able to resolve any violations about neutrality.